Knowledge and Uptake of Preconception Rhesus Factor Screening Among Pregnant Women In Ibadan, Nigeria - Opayele, Blessing Funke; Okpaleke, Miriam Hilda; Ndikom, Chizoma M. (Journal of Midwifery, 2024)
Rhesus incompatibility is major factor contributing to perinatal morbidity and mortality. Therefore, need to determine the knowledge and uptake of preconception rhesus factor screening among pregnant women in Ibadan, Nigeria. A descriptive cross-sectional design was used and a total number of 400 pregnant women were recruited by multistage sampling from 3 LGA in Ibadan. Data were analyzed using descriptive statistics and presented in frequency tables, percentages and bar chart. The findings revealed that most 247 (61.8%) of the pregnant women's age group was between 25-34 years with the mean age of 29.1Â±5.3. More than half 225 (53.6%) of the respondents were aware that the Rhesus factor is found on the surface of the red blood and 265 (66.3%) of the respondents were not aware of preconception rhesus factor screening. This is evident as most 332 (83%) of the pregnant women were not screened before their first pregnancy, 160 (40%) never heard about rhesus incompatibility, more than half 224 (56%) do not know the precautions that rhesus negative mother should take. The prevalence of rhesus negative individuals among the pregnant women in the study population area was 6.4, while 129 (32.3%) do not know their rhesus status. There is significant association between respondentsâ€™ knowledge of rhesus factor and preconception rhesus factor screening (p = 0.0000, X2 = 190.966). Based on these findings, it was recommended that health care providers should use every contact with people as an opportunity to educate not just women, but also men and every couple about rhesus factor screening and rhesus incompatibility.